PERBANDINGAN EFIKASI DAN KEAMANAN PENGGUNAAN FEBUXOSTAT DAN ALLOPURINOL PADA PASIEN GOUT - Hendra Herman; Sukmawati Sukmawati; Andi Desiah Pranada (As-Syifaa Jurnal Farmasi, 2021)
Febuxostat and allopurinol are xanthine oxidase inhibitors to reduce uric acid levels. The research aimed to determine the differences in efficacy and safety of using febuxostat and allopurinol for gout patients. This research was conducted using a narrative review method for articles obtained from the PubMed and Willey databases published in 2010-2021. From the article exploration, 5 articles were reviewed showing that the determination of drug efficacy was seen by monitoring the changes in uric acid levels for 6 months from the beginning of drug use. Febuxostat and allopurinol had good efficacy in achieving target uric acid levels < 6 mg/dL, however, febuxostat was superior to allopurinol in usual doses. Febuxostat 80 mg had superior efficacy to febuxostat 40 mg, while febuxostat 40 mg had superior efficacy to allopurinol 300 mg (p < 0.05). For safety, febuxostat and allopurinol possessed similar side effects in the form of upper respiratory tract infection, diarrhea, headache, nausea and vomiting.